Dampak Variasi Genetik terhadap Respon Terapi dan Potensi Hemolisis Anemia dari Penggunaan Primakuin melalui Pendekatan Farmakogenetika - Rahman Sumani Sianu; Annisa Abdi Ghifari; Muhammad Ma’ruf; Eka Yuni Nur Jannah; Putri Ayu Lestari (Herbal Medicine Journal, 2026)
Primaquine is essential for radical cure of Plasmodium vivax malaria but poses hemolysis risk in G6PD-deficient individuals and shows variable therapeutic responses. Genetic polymorphisms in drug-metabolizing enzymes and transporters contribute to these inter-individual variations. To investigate genetic variants in G6PD, SLCO2B1, and MAOA genes that influence primaquine safety and efficacy, and to assess their clinical implications for personalized antimalarial therapy. Method the database used in this study is PhramGKB. Genetic polymorphisms in four candidate genes were analyzed for associations with hemolysis, anemia, therapeutic efficacy, and malaria recurrence. Statistical analyses determined the strength and significance of genotype-phenotype associations. Result G6PD variants rs1050828 and rs1050829 showed strong associations with hemolysis (p<0.01) and anemia (p=0.001). SLCO2B1 variant rs12422149 was associated with reduced chloroquine-primaquine efficacy (p=0.01). MAOA variant rs6323 increased malaria recurrence risk (p=0.03). Conclusion multiple genetic variants significantly impact primaquine safety and efficacy. These findings support pharmacogenetic-guided personalized antimalarial therapy to optimize outcomes and minimize adverse events, contributing to malaria elimination efforts.